Paparan timbal dalam urin remaja pada kejadian gangguan sistem saraf dan keseimbangan di kecamatan Curug - Dhia Syarifa Levanta; Izza Hananingtyas (Public Health Risk Assesment Journal, 2023)
In the production process, there are several industries that use Pb in their production process, one of which is in the battery smelting process. The explanation that the source of Pb pollution in Kec. Curug comes from battery recycling industry activities. One of the groups in society that is at risk of being affected is early adolescence which at that age is a period of rapid growth and development, both physically, psychologically and intellectually. Pb accumulation in body tissues, especially in the nerves will cause disturbances in the nervous system both structurally and functionally. It is known that it affects different parts of the brain, one of which is the cerebellum which has the function of coordinating adjustments quickly and automatically by maintaining body balance. The population of this study were 92 early adolescents in two high schools in Permata, Kec. Waterfall with a sample of 52 people. Examination of balance disorders is done with the Romberg test. This study used a cross-sectional study design with this type of observational research. In conclution, (92.3%) early teens urine contain Lead (Pb) are still below the specified Treshold Value (<50 µg/L). The emergence of complaints of the central nervous system and the balance disorder in early teens can be caused by other factors.